Введение в класс трансдисциплинарных онтолого-управляемых систем исследовательского проектирования - Палагин, А.В. (Управляющие системы и машины, 2016)
Рассмотрен класс систем исследовательского проектирования, основанных на использовании парадигм трансдисциплинарности, онтологического управления и целенаправленного развития. Предназначен прежде всего для проектирования новых прикладных интеллектуальных информационных систем и технологий. Розглянуто клас систем дослідницького проектування, заснованих на використанні парадигм трансдисциплінарності, онтологічного керування та цілеспрямованого розвитку. Призначений насамперед для проектування нових прикладних інтелектуальних інформаційних систем і технологій. The research design systems (RDS) hold a special place among information technology systems. Their operation is based on clearly formulated objectives, regulations and criteria in feedback mode with external environment deepening the knowledge in the subject field during the design process. The basis of designing with the use of RDS is the system integration technology, the essence of which is building the higher-level components of the projected object from the lower-level components and systematizing the typical project solutions. It is expected that this class of systems will be built as ontology-driven ones in the conditions of partially defined information about the subject area and about the subject of design. It is considered a good practice to develop and apply such systems while implementing the complex transdiscipline projects when there are no efficient methods to integrate knowledge of different subject fields, which could realize the processes of building a stable cluster for convergence of scientific disciplines and technologies with high-level synergism. The concept of the virtual research environment was formulated as a network tools complex, information analytical and administrative subsystems that accompany the process of building the new equipment and technologies at all stages of the life cycle. The examples of promising virtual systems include the research centers and labs. Accordingly, the systems of research design built on the noospheric concept basis (such as transdisciplinarily, evolutionism, ontological control, multi-level representation of knowledge, virtuality) open the way for great opportunities for their implementation in scientific research.